Inhibition of NF-κB Signaling Reduces the Stemness Characteristics of Lung Cancer Stem Cells - Zakaria, Norashikin; Mohd Yusoff, Narazah; Zakaria, Zubaidah; Widera, Darius; Yahaya, Badrul Hisham (Frontiers in Oncology, 2018)
Cancer stem cells (CSCs) are a subpopulation of cancer cells that play a pivotal role in tumour development, invasion, metastasis, and recurrence. We and others have reported significant involvement of the NF-κB pathway in regulating CSCs of non-small cell lung cancer (NSCLC). In this study, we evaluated the effects of NF-κB inhibition on self-renewal, stemness, migration, and expression of genes involved in the epithelial to mesenchymal transition (EMT) and apoptosis resistance in lung CSCs. Different concentrations of the NF-κB inhibitor BMS-345541 (0.4, 4.0, and 10.0 µM), an inhibitor the NF-κB upstream kinase IKKβ, were used to treat both lung CSCs (CD166+CD44+, CD166+EpCAM+) and non-CSC NSCLC cells (CD166¯CD44¯, CD166¯EpCAM¯) in A549 and H2170 cell lines. We assessed the impact of BMS-345541 on the ability to form tumorspheres (self-renewal assay), expression of stemness genes (SOX2, OCT4, NANOG, SCA-1, and KLF4), migration, and expression of EMT and apoptosis-related genes. Inhibition of NF-κB by BMS-345541 effectively reduced the stemness, self-renewal, and migration capacity of lung CSCs. Moreover, expression of genes involved in the EMT (SNAI1 and TWIST) and apoptosis resistance (BCL-2, BAX, and BIRC5) was significantly reduced following the treatments, suggesting that NF-κB inhibition is sufficient to prevent the EMT and induce apoptosis in lung CSCs. Our findings suggest that NF-κB inhibition could reduce the capability of CSCs to maintain their population within the tumour mass, potentially decelerating cancer progression, relapse, and chemotherapy resistance.